La fine di un mondo La deriva dell'ordine liberale - Magri, Paolo; Colombo, Alessandro (Ledizioni, 2019)
Also in the last year the signs of decomposition of the political, economic and institutional world conceived at the end of the Second World War and definitively freed from the end of the cold war have multiplied. Meanwhile, the advent of Donald Trump as president of the United States has introduced an unprecedented tension between the US and the international order they themselves produced. More generally, the growth of China and the renewed assertiveness of Russia seem to herald a new phase of the reflux of Western impact on the rest of the world. Above all, a variegated dispute over legitimacy has affected the liberal orientation of the post-bipolar order, with ever more profound consequences for the holding of the multilateral fabric of international coexistence, international organizations and even the institutional set-up of individual states. The ISPI 2019 Report questions this upheaval, both in the political and economic dimensions. The first part of the volume is dedicated to the global context and its repercussions on Europe, while the second is addressed as usual to Italian foreign policy.
Description based on print version record.
KU Open Services
Keywords: Political Science / International Relations; Political science; Electronic books